PENGARUH METODE PEMBELAJARAN INKLUSI TERHADAP HASIL BELAJAR FORWARD ROLL PADA PESERTA DIDIK SMPN 3 - Wood, Benny; Triansyah, Andika; Hidasari, Fitriana Puspita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "whether there is influence of inclusive learning method to learning result of forward roll roll gymnastics. The purpose of this study is to determine the effect of inclusion learning methods on the learning results of forward roll roll gymnastics. The population in this study amounted to 227 people. Sampling using purposive sampling technique is the determination of samples with certain considerations which amounted to 58 people. The method used is experiment with pre-experimental design. Data analysis through IBM SPSS 21 t test. Data analysis was done by t-test analysis, but beforehand was done normality and homogeneity test. Normally distributed data with pretest significance of 0.170 and posttest 0.062 with each indicator greater than 0.050. Based on the result of the influence of inclusion learning method toward the forward roll roll gymnastics learning is known the mean pretest level 49,76 and posttest 86,48, with percentage of increase 36,72. This means that the influence of the inclusion learning method on the forward roll roll gymnastics learning result has increased.Â Keywords: Inclusion, Forward Roll.Â